Clinical profile and initial treatment of non-small cell lung cancer: a retrospective cohort study at the Uganda Cancer Institute. - Kibudde, Solomon; Kirenga, Bruce James; Nabwana, Martin; Okuku, Fred; Walusansa, Victoria; Orem, Jackson (African Health Sciences, 2021)
Lung cancer is a major global public health burden constituting 11.6% of all new cancer diagnoses and 18.4% of all cancer-related mortality. Purpose: To describe the clinical profile and initial treatment of non-small cell lung cancer in Uganda. Methods: We reviewed charts of a cohort of patients with a histologically confirmed diagnosis of non-small cell lung cancer, treated between January 2013 and November 2015 at the Uganda Cancer Institute. Results: A total of 74 patients met the inclusion criteria. The median age was 56 years (IQR 47-70), with 16.2% below the age 45 years, and 51% were female. Only 10 percent were active smokers and the most frequent histological subtype was adenocarcinoma (71%). The majority (91.9%) had stage IV disease at diagnosis and frequent metastases to contralateral lung, liver, and bones. Twenty-seven (27) patients received platinum-based chemotherapy, while 27 patients received erlotinib, and only 4 patients received palliative thoracic radiotherapy. The median survival time was 12.4 months, and the overall response rate was 32.7%. There was no survival difference by type of systemic treatment, and on multivariate analysis, poor performance status was predictive of adverse outcomes (p < 0.001). Conclusions: Patients with non-small cell lung cancer in Uganda frequently presented with late-stage disease at diagnosis. The majority of patients were female, never-smokers, and had predominantly adenocarcinoma subtype.
Keywords: Non-small cell lung cancer; Uganda; Uganda Cancer Institute; erlotinib; lung cancer